Overview of Four Prescription Monitoring/Review Programs in Canada. (2014) - Furlan, Andrea D; MacDougall, Peter; Pellerin, Denise; Shaw, Karen; Spitzig, Doug; Wilson, Galt; Wright, Janet
Abstract : BACKGROUND: Prescription monitoring or review programs collect information about prescription and dispensing of controlled substances for the purposes of monitoring, analysis and education. In Canada, it is the responsibility of the provincial institutions to organize, maintain and run such programs. OBJECTIVE: To describe the characteristics of four provincial programs that have been in place for >6 years. METHODS: The managers of the prescription monitoring/review programs of four provinces (British Columbia, Alberta, Saskatchewan and Nova Scotia) were invited to present at a symposium at the Canadian Pain Society in May 2012. In preparation for the symposium, one author collected and summarized the information. RESULTS: Three provinces have a mix of review and monitoring programs; the program in British Columbia is purely for review and education. All programs include controlled substances (narcotics, barbiturates and psychostimulants); however, other substances are differentially included among the programs: anabolic steroids are included in Saskatchewan and Nova Scotia; and cannabinoids are included in British Columbia and Nova Scotia. Access to the database is available to pharmacists in all provinces. Physicians need consent from patients in British Columbia, and only professionals registered with the program can access the database in Alberta. The definition of inappropriate prescribing and dispensing is not uniform. Double doctoring, double pharmacy and high-volume dispensing are considered to be red flags in all programs. CONCLUSIONS: There is variability among Canadian provinces in managing prescription monitoring/review programs.